Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery
By covering the lithium phosphate layer on the surface of lithium-rich lithium ferrate material, the air stability and safety problems of lithium-rich cathode material are solved, and more efficient lithium-replenishment effect and battery performance are achieved.
Patent Information
- Application Number
- CN202411975309.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-rich cathode materials have problems of poor air stability and relatively poor safety, which limits their application in lithium supplement materials.
By covering the surface of lithium-pyrophosphate with lithium phosphate on the surface of lithium-rich lithium ferrate, the air stability and safety stability are improved, and the lithium supplement effect is improved.
It improves the air stability and safety stability of lithium supplements, improves the lithium ion transmission and conduction performance, enhances the lithium supplement effect of lithium supplements, and thus improves the electrochemical performance and safety of positive electrode sheets and secondary batteries.
Smart Images

Figure CN119725487A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to a lithium supplement and a preparation method thereof, a positive electrode sheet, and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in energy storage fields such as new energy vehicle batteries. During the first charging process of lithium-ion batteries, the organic electrolyte will be reduced and decomposed on the surface of the negative electrode such as graphite to form a solid electrolyte interphase (SEI) film, which permanently consumes a large amount of lithium from the positive electrode, resulting in a low initial Coulombic efficiency (ICE) of the first cycle, reducing the capacity and energy density of the lithium battery.
[0003] In order to solve the problem of low coulombic efficiency of lithium-ion batteries, lithium supplementation is needed to make up for the irreversible loss of lithium. At present, the main methods of lithium supplementation are negative electrode lithium supplementation and positive electrode lithium supplementation. Compared with the difficulty and investment of negative electrode lithium supplementation, positive electrode lithium supplementation has become the main way of lithium supplementation because high-capacity materials can be added during the positive electrode slurry process. The ideal positive electrode lithium supplementer needs to meet multiple conditions, such as good air stability, high specific energy and volume energy density, lithium stripping potential and lithium insertion potential between the working of positive electrode materials, and compatibility with the current common manufacturing process and battery system.
[0004] Currently, the common positive electrode lithium supplements are mainly lithium-rich positive electrode materials, such as lithium-rich lithium iron oxide and lithium-rich lithium nickel oxide, etc. However, these lithium-rich positive electrode materials have problems such as poor air stability, easy decomposition, and relatively poor safety. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate containing the lithium supplement agent and a secondary battery containing the positive electrode plate, aiming to solve the technical problems of poor air stability and relatively poor safety of lithium-rich positive electrode materials in the related technology.
[0006] In a first aspect, an embodiment of the present application provides a lithium supplement, which includes: a lithium-rich lithium iron oxide material, and a coating layer coated on the surface of the lithium-rich lithium iron oxide material; wherein the material of the coating layer includes: lithium pyrophosphate.
[0007] In the technical solution of the embodiment of the present application, a coating layer having lithium pyrophosphate is coated on the surface of the lithium iron ore-rich material. On the one hand, the lithium pyrophosphate is an ion conductor, which provides a deintercalation channel for lithium ions while providing part of the capacity, thereby facilitating the movement of lithium ions during the charge-discharge process of the battery and improving the lithium ion transmission and conduction performance. On the other hand, the lithium pyrophosphate protects the lithium iron ore-rich material, reduces the contact between the lithium iron ore-rich material and the air, thereby improving the air stability of the lithium iron ore-rich material, achieving the effect of improving the air stability and safety stability of the lithium supplement agent, and enhancing the lithium supplement effect of the lithium supplement agent.
[0008] In some embodiments, the lithium ferrite-rich material includes titanium.
[0009] In the above embodiment, by doping the lithium-rich lithium iron phosphate material with titanium, during the charge-discharge process, it is beneficial to suppress the collapse and phase change of the crystal structure of the lithium-rich lithium iron phosphate material, thereby improving the material stability of the lithium supplement; at the same time, the doping of titanium can also adjust the lattice electric field, suppress cation mixing, thereby optimizing the ion diffusion channel, making the lithium ion diffusion more orderly, and accelerating the diffusion rate of lithium ions, thereby improving the capacity and lithium supplement efficiency of the lithium supplement; further, the doping of titanium is beneficial to improving the electronic conductivity of the lithium-rich lithium iron phosphate material, thereby improving the conductivity of the lithium supplement; in addition, the doping of titanium is beneficial to enhancing the chemical bond energy of the lithium-rich lithium iron phosphate material, reducing the structural damage and performance attenuation of the lithium supplement at high temperature, and thus helping to improve the safety and reliability of the battery in a high temperature environment.
[0010] In some embodiments, the thickness of the coating layer is 10 nm to 50 nm, and / or the coating layer has a coverage greater than or equal to 94%.
[0011] In the above embodiment, by controlling the thickness of the coating layer within the above range, it is beneficial for lithium pyrophosphate to effectively coat the lithium-rich lithium ferrite material, reducing the contact between the lithium-rich lithium ferrite material and air. By controlling the coating rate of the coating layer to be greater than or equal to 94%, the coating integrity of the lithium pyrophosphate on the lithium-rich lithium ferrite material can be improved, further reducing the contact between the lithium-rich lithium ferrite material and air.
[0012] In a second aspect, the present application provides a method for preparing a lithium supplement, comprising:
[0013] Provide lithium-rich lithium iron oxide materials;
[0014] A coating layer is formed on the surface of the lithium-rich lithium ferrite material, and the material of the coating layer includes: lithium pyrophosphate.
[0015] In the technical solution of the embodiment of the present application, a lithium supplement can be prepared by forming a coating layer on the surface of a lithium-rich ferrite material, and the preparation method is simple and easy. The surface of the lithium-rich ferrite material of the lithium supplement prepared in this way is coated with a coating layer having lithium pyrophosphate. On the one hand, the lithium pyrophosphate is an ion conductor, which provides a deintercalation channel for lithium ions while providing part of the capacity, facilitates the movement of lithium ions during the battery charge-discharge process, and improves the lithium ion transmission and conduction performance. On the other hand, the lithium pyrophosphate protects the lithium-rich ferrite material, reduces the contact between the lithium-rich ferrite material and the air, thereby improving the air stability of the lithium-rich ferrite material, achieving the effect of improving the air stability and safety stability of the lithium supplement, and enhancing the lithium supplement effect of the lithium supplement.
[0016] In some embodiments, the step of providing a lithium-rich lithium ferrite material comprises:
[0017] providing a first lithium salt and a ferrous salt;
[0018] The first lithium salt and the ferrous salt are mixed and calcined under the protection of protective gas to obtain the lithium-rich lithium ferrite material.
[0019] In the above embodiment, after the first lithium salt and the ferrous salt are mixed, they are calcined under the protection of a protective gas, so as to facilitate more effective fusion of lithium and iron elements and reduce the generation of impurities, thereby improving the product performance of the obtained lithium supplement.
[0020] In some embodiments, the first lithium salt includes lithium nitrate, the ferrous salt includes ferrous oxalate, the ferrous oxalate includes titanium, and the total amount of lithium in the first lithium salt to the iron and titanium in the ferrous salt is (5.0~5.3):1.
[0021] In the above embodiment, lithium nitrate and ferrous oxalate are used as raw materials and calcined under the protection of protective gas. Compared with the use of lithium salts or lithium oxides and trivalent iron oxides to obtain lithium-rich lithium iron oxide in the related art, on the one hand, there is no need to use a large amount of high-cost lithium oxide, and the cost is lower; on the other hand, when lithium nitrate and ferrous oxalate react, the calcination temperature is low and the calcination time is shorter, which is beneficial to saving energy; at the same time, due to the redox reaction between lithium nitrate and ferrous oxalate, nitrogen oxides are reduced to nitrogen gas, which is beneficial to reducing the generation of nitrogen oxides, reducing environmental pollution and corresponding governance costs; in addition, the lithium nitrate and ferrous oxalate are used as raw materials, and the lithium-rich lithium iron oxide material prepared by calcining under the protection of protective gas has less agglomeration, making subsequent crushing more convenient, and it is easy to prepare lithium-rich lithium iron oxide materials with a large specific surface area, which is beneficial to improving the electrochemical properties of lithium-rich lithium iron oxide materials and enhancing the lithium replenishment effect of lithium replenishers. In addition, when the ferrous salt includes titanium, it is convenient to introduce titanium into the lithium-rich lithium ferrite material, which is beneficial to improving the electrochemical properties and thermal stability of the lithium-rich lithium ferrite material and further improving the lithium supplementation effect.
[0022] In some embodiments, calcination includes a first stage and a second stage performed sequentially;
[0023] In the first stage, the calcination temperature is 200°C to 400°C, and the calcination holding time is 3h to 5h;
[0024] In the second stage, the calcination temperature is 600° C. to 700° C., and the calcination holding time is 4 h to 6 h.
[0025] In the above embodiment, by setting up two calcination stages, it is beneficial to allow the redox reaction of the first lithium salt and the ferrous salt to fully proceed in the first stage while allowing the generated water vapor, carbon dioxide, nitrogen oxides, etc. to be discharged as soon as possible, thereby reducing the reaction of these gases with lithium; in the second stage, by further increasing the reaction temperature, it is beneficial to allow the first lithium salt and the ferrous salt to further fully react, thereby obtaining a lithium-rich lithium ferrate material with improved purity.
[0026] In some embodiments, forming a coating layer on the surface of the lithium ferrite-rich lithium material includes:
[0027] The second lithium salt, the pyrophosphate source, and the first solvent are mixed to obtain a first reaction material;
[0028] The lithium iron oxide material rich in lithium is mixed with the first reaction material, and subjected to a first impurity removal treatment to obtain a lithium supplement agent.
[0029] In the above embodiment, by mixing the lithium iron phosphate-rich material with the first reaction material, it is beneficial to deposit the lithium pyrophosphate on the surface of the lithium iron phosphate-rich material while the second lithium salt and the pyrophosphate source react to obtain lithium pyrophosphate, thereby forming a coating layer on the surface of the lithium iron phosphate-rich material, and obtaining a lithium supplement through a first impurity removal treatment.
[0030] In some embodiments, the first impurity removal treatment includes evaporating the first solvent, solid-liquid separation, drying, screening and iron removal.
[0031] In the above embodiment, by evaporating the first solvent, it is beneficial to evaporate and remove the volatile gas generated after the lithium-rich lithium iron oxide material and the first reaction material are mixed, so as to obtain lithium pyrophosphate-coated lithium-rich lithium iron oxide with higher purity; at the same time, by evaporating and removing the first solvent, the lithium pyrophosphate is gradually precipitated and coated on the surface of the lithium-rich lithium iron oxide material, thereby forming a coating layer, and then through solid-liquid separation, drying, screening and iron removal treatment, a lithium supplement with higher purity is obtained.
[0032] In some embodiments, the preparation method of the lithium supplement meets at least one of the following conditions:
[0033] (1) The molar ratio of the lithium element in the lithium iron oxide material, the second lithium salt and the pyrophosphate ion in the pyrophosphate source is 1: (0.1-0.15): (0.025-0.04);
[0034] (2) The first solvent includes: ethanol;
[0035] (3) the second lithium salt comprises at least one of lithium acetate, lithium chloride, lithium nitrate and lithium citrate;
[0036] (4) the pyrophosphate source comprises at least one of pyrophosphoric acid, ammonium pyrophosphate and ammonium hydrogen pyrophosphate;
[0037] (5) The temperature for evaporating the first solvent is 80°C to 120°C.
[0038] In the above embodiment, by controlling the amount of lithium ferrite-rich lithium material, the lithium element in the second lithium salt and the pyrophosphate in the pyrophosphate source to be 1: (0.1~0.15): (0.025~0.04), it is beneficial to form an appropriate amount of lithium pyrophosphate as a coating layer on the surface of the lithium ferrite-rich lithium material, so that the coating is relatively complete, and the contact between the lithium ferrite-rich lithium material and the air is effectively reduced, thereby effectively improving the capacity and stability of the lithium supplement when in use. By using ethanol as the first solvent, the boiling point is low and it is easy to evaporate. By using at least one of the above lithium salts as the second lithium salt, the anion of the second lithium salt can be decomposed and / or volatilized, and the precipitation and crystallization of lithium pyrophosphate can be achieved by utilizing the azeotropic principle of the first solvent and the acid corresponding to the anion in the second lithium salt during the reaction of the second lithium salt and the pyrophosphate source, and heterogeneous nucleation is easy to occur on the surface of the lithium ferrite-rich lithium material. During the heterogeneous nucleation of lithium pyrophosphate on the surface of lithium iron-rich material, as the first solvent evaporates, lithium ions and pyrophosphate slowly combine, which can keep the supersaturation of lithium pyrophosphate low, so that lithium pyrophosphate slowly crystallizes and deposits on the surface of lithium iron-rich material, making the coating more dense and complete. At least one of the above-mentioned pyrophosphate and pyrophosphate salts is used as the pyrophosphate source, and the products other than lithium pyrophosphate generated by the reaction of the second lithium salt and the pyrophosphate source are easy to decompose and volatilize, which facilitates the precipitation and crystallization of lithium pyrophosphate on the surface of lithium iron-rich material while reducing the introduction of impurities. By controlling the evaporation temperature to 80°C~120°C, the first solvent and the anion of the second lithium salt are facilitated to co-azeotropy.
[0039] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector, and a positive electrode material disposed on at least one side of the current collector along its thickness direction, wherein the positive electrode material comprises the lithium supplement agent as described in the first aspect.
[0040] In this embodiment, the positive electrode plate contains the above-mentioned lithium replenishing agent, so that effective lithium replenishment can be achieved and the safety stability and air stability of the battery during the lithium replenishment process can be improved.
[0041] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising: a positive electrode plate, a negative electrode plate and a separator; wherein the positive electrode plate is the positive electrode plate as described in the third aspect.
[0042] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and the positive electrode plate includes the above-mentioned lithium supplement agent. Therefore, the secondary battery has higher safety stability and air stability during the lithium supplement process.
[0043] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0045] Figure 1 A schematic flow chart of a method for preparing a lithium supplement provided in an embodiment of the present application. DETAILED DESCRIPTION
[0046] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0048] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0049] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0050] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0051] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0052] In the currently used positive electrode lithium supplement materials, for example, lithium-rich nickel oxide (Li 2 NiO 2 )、LiFePO4(Li 5 FeO 4 ), etc., have problems such as poor air stability and poor safety, which limit their application in lithium supplement materials.
[0053] In order to solve the technical problems of poor stability and relatively poor safety stability of the above-mentioned lithium-rich positive electrode materials in the air, the present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate, and a secondary battery, wherein a coating layer having lithium pyrophosphate is coated on the surface of a lithium-rich lithium ferrite material, and the lithium pyrophosphate is an ion conductor, which provides a deintercalation channel for lithium ions while providing part of the capacity, thereby facilitating the movement of lithium ions during the battery charge-discharge process and improving the lithium ion transmission and conduction performance. On the other hand, the lithium pyrophosphate protects the lithium-rich lithium ferrite material, reduces the contact between the lithium-rich lithium ferrite material and the air, thereby improving the air stability of the lithium-rich lithium ferrite material, achieving the effect of improving the air stability and safety stability of the lithium supplement agent, and enhancing the lithium supplement effect of the lithium supplement agent, thereby improving the electrochemical performance (such as battery capacity and cycle performance), air stability and safety stability of the positive electrode plate and the secondary battery.
[0054] In a first aspect, an embodiment of the present application provides a lithium supplement, comprising: a lithium-rich lithium iron oxide material, and a coating layer coated on the surface of the lithium-rich lithium iron oxide material;
[0055] Wherein, the material of the coating layer includes: lithium pyrophosphate.
[0056] In some embodiments, the lithium ferrite-rich material includes titanium.
[0057] In the above embodiment, by doping the lithium-rich lithium iron phosphate material with titanium, during the charge-discharge process, it is beneficial to suppress the collapse and phase change of the crystal structure of the lithium-rich lithium iron phosphate material, thereby improving the material stability of the lithium supplement; at the same time, the doping of titanium can also adjust the lattice electric field, suppress cation mixing, thereby optimizing the ion diffusion channel, making the lithium ion diffusion more orderly, and accelerating the diffusion rate of lithium ions, thereby improving the capacity and lithium supplement efficiency of the lithium supplement; further, the doping of titanium is beneficial to improving the electronic conductivity of the lithium-rich lithium iron phosphate material, thereby improving the conductivity of the lithium supplement; in addition, the doping of titanium is beneficial to enhancing the chemical bond energy of the lithium-rich lithium iron phosphate material, reducing the structural damage and performance attenuation of the lithium supplement at high temperature, and thus helping to improve the safety and reliability of the battery in a high temperature environment.
[0058] In some embodiments, the chemical formula of the lithium-rich lithium ferrite material is: Li x Fe y Ti (1-y) O 4 , wherein x is 5.05 to 5.2, and y is 0.978 to 0.995. For example, x can be 5.05, 5.1 or 5.2, and y can be 0.978, 0.980, 0.982, 0.985, 0.988, 0.990 or 0.995, etc.
[0059] In the above embodiment, the lithium-rich lithium ferrite material is doped with Ti element, and the molar ratio of Ti element to Fe element is (0.005~0.022): (0.995~0.978), which is beneficial to improving the stability of the lithium supplement agent while improving the capacity and lithium supplement efficiency of the lithium supplement agent. As the molar ratio of Ti element to Fe element increases or decreases, it is not conducive to further improving the comprehensive performance of the lithium-rich lithium ferrite material, such as electrochemical performance and thermal stability.
[0060] In some embodiments, the chemical formula of the lithium supplement is: Li x Fe y Ti (1-y) O 4 @Li m (P 2 O 7 ) n; wherein x is 5.05 to 5.2, y is 0.978 to 0.995, m is 0.1 to 0.15, and n is 0.025 to 0.04. For example, x can be 5.05, 5.1, or 5.2, y can be 0.978, 0.980, 0.982, 0.985, 0.988, 0.990, or 0.995, m can be 0.1, 0.11, 0.12, 0.13, 0.14, or 0.15, and n can be 0.025, 0.026, 0.028, 0.03, 0.032, 0.034, 0.035, 0.037, 0.038, 0.039, or 0.04, etc.
[0061] In some embodiments, the coating layer has a thickness of 10 nm to 50 nm. For example, the coating layer has a thickness of 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.
[0062] In the above embodiment, by controlling the thickness of the coating layer within the above range, it is beneficial for lithium pyrophosphate to effectively coat the lithium-rich lithium ferrite material, thereby reducing the contact between the lithium-rich lithium ferrite material and the air.
[0063] In some embodiments, the coating layer has a thickness of 19 nm to 48 nm.
[0064] In the above embodiment, further controlling the thickness of the coating layer is beneficial to more effectively coating the lithium pyrophosphate on the lithium-rich lithium iron oxide material, further reducing the contact between the lithium-rich lithium iron oxide material and air, and maintaining good lithium ion transmission and conduction properties.
[0065] In some embodiments, the coating has a coverage greater than or equal to 94%. The coverage refers to the percentage of the coverage area of the coating on the surface of the lithium-rich lithium iron oxide material to the total surface area of the lithium-rich lithium iron oxide material. For example, the coating may have a coverage of 94%, 95%, 96%, 97%, 98%, or 99%.
[0066] In the above embodiment, by controlling the coating rate of the coating layer to be greater than or equal to 94%, it is beneficial to improve the coating completeness of the lithium pyrophosphate on the lithium-rich lithium ferrite material and further reduce the contact between the lithium-rich lithium ferrite material and the air.
[0067] In some embodiments, the coverage of the coating layer is 94.1% to 99.1%.
[0068] In the above embodiment, by controlling the coating rate of the coating layer within the range of 94.1% to 99.1%, the coating integrity of the lithium pyrophosphate on the lithium-rich lithium iron oxide material is improved while maintaining good lithium ion transmission and conduction performance.
[0069] In some embodiments, the compacted density of the lithium supplement is 2.89 g / mL to 3.14 g / mL, preferably 2.89 g / mL to 3 g / mL.
[0070] For example, the compacted density of the lithium supplement can be 2.89 g / mL, 2.90 g / mL, 2.91 g / mL, 2.92 g / mL, 2.93 g / mL, 2.94 g / mL, 2.95 g / mL, 2.96 g / mL, 2.97 g / mL, 2.99 g / mL, 3.0 g / mL, 3.05 g / mL, 3.08 g / mL, 3.1 g / mL, 3.11 g / mL, 3.12 g / mL, 3.13 g / mL or 3.14 g / mL, etc.
[0071] In the above embodiments, controlling the compaction density of the lithium supplement agent is beneficial to maintaining a high energy density of the lithium supplement agent, thereby improving the lithium supplement effect.
[0072] In some embodiments, the tap density of the lithium supplement is 1.68 g / mL to 1.89 g / mL, preferably 1.68 g / mL to 1.74 g / mL.
[0073] For example, the tap density of the lithium supplement is 1.68 g / mL, 1.70 g / mL, 1.72 g / mL, 1.75 g / mL, 1.76 g / mL, 1.78 g / mL, 1.79 g / mL, 1.80 g / mL, 1.82 g / mL, 1.85 g / mL, 1.86 g / mL, 1.88 g / mL or 1.89 g / mL, etc.
[0074] In some embodiments, the specific surface area of the lithium supplement is 5.68 m 2 / g~8.49 m 2 / g, preferably 7.27m 2 / g~7.45 m 2 / g, which is beneficial to improve the effect of lithium supplementation.
[0075] For example, the specific surface area of the lithium supplement is 5.68 m 2 / g, 5.70 m 2 / g, 5.72 m 2 / g, 5.75 m 2 / g, 5.78 m 2 / g, 5.79 m 2 / g, 5.82 m 2 / g, 5.85 m 2 / g, 5.89 m 2 / g, 5.92 m 2 / g、5.94 m 2 / g、5.98 m 2 / g、6.0 m 2 / g、6.05 m 2 / g、6.08 m 2 / g、6.12 m 2 / g、6.15 m 2 / g、6.18 m 2 / g、6.19 m 2 / g、6.21 m 2 / g、6.25 m 2 / g、6.28 m 2 / g、6.29 m 2 / g、6.32 m 2 / g、6.35 m 2 / g、6.37 m 2 / g、6.39 m 2 / g、6.45 m 2 / g、6.48 m 2 / g、6.52 m 2 / g、6.59 m 2 / g、6.68 m 2 / g、6.75 m 2 / g、6.79 m 2 / g、6.85 m 2 / g、6.89 m 2 / g、6.94 m 2 / g、6.98 m 2 / g、7.01 m 2 / g、7.08 m 2 / g、7.12 m 2 / g、7.15 m 2 / g、7.19 m 2 / g、7.25 m 2 / g、7.28 m 2 / g、7.31 m 2 / g、7.35 m 2 / g、7.37 m 2 / g、7.39 m 2 / g、7.45 m 2 / g、7.48 m 2 / g、7.51 m 2 / g、7.56 m 2 / g、7.58 m 2 / g、7.61 m 2 / g、7.64 m2 / g, 7.69 m 2 / g, 7.72 m 2 / g, 7.76 m 2 / g, 7.79 m 2 / g, 7.83 m 2 / g, 7.85 m 2 / g, 7.89 m 2 / g, 7.92 m 2 / g, 7.94 m 2 / g, 7.96 m 2 / g, 7.99 m 2 / g, 8.01 m 2 / g, 8.05 m 2 / g, 8.08 m 2 / g, 8.1 m 2 / g, 8.13 m 2 / g, 8.15 m 2 / g, 8.16 m 2 / g, 8.19 m 2 / g, 8.25 m 2 / g, 8.29 m 2 / g, 8.34 m 2 / g, 8.35 m 2 / g, 8.37 m 2 / g, 8.40 m 2 / g, 8.45 m 2 / g or 8.49 m 2 / g, etc.
[0076] In some embodiments, the pH value of the lithium supplement is 9.01-10.35, optionally 9.01-9.89.
[0077] In the above embodiment, the pH value of the lithium supplement agent is closer to neutral, which reduces the residual alkali on the surface of the lithium supplement agent, is conducive to fully utilizing the capacity of the lithium supplement agent, and improves the safety and stability of the lithium supplement agent during lithium supplementation.
[0078] For example, the pH value of the lithium supplement can be 9.01, 9.05, 9.17, 9.15, 9.16, 9.19, 9.25, 9.28, 9.34, 9.36, 9.38, 9.40, 9.43, 9.46, 9.48, 9.5, 9.52, 9.55, 9.57, 9.59, 9.62, 9.64, 9. 68, 9.7, 9.73, 9.78, 9.8, 9.85, 9.88, 9.9, 9.94, 9.97, 10.0, 10.05, 10.09, 10.12, 10.15, 10.16, 10.18, 10.2, 10.23, 10.25, 10.28, 10.3, 10.34 or 10.35, etc.
[0079] In some embodiments, the D10 particle size of the lithium supplement is 0.32 μm to 0.79 μm, the D50 particle size is 1.67 μm to 5.78 μm, and the D90 particle size is 9.01 μm to 14.67 μm.
[0080] For example, the D10 particle size of the lithium supplement agent can be 0.32 μm, 0.35 μm, 0.38 μm, 0.4 μm, 0.42 μm, 0.45 μm, 0.48 μm, 0.47 μm, 0.5 μm, 0.52 μm, 0.55 μm, 0.56 μm or 0.57 μm, and the D50 particle size of the lithium supplement agent can be 1.67 μm, 1.69 μm, 1.71 μm, 1.75 μm, 1.78 μm, 1.8 μm, 1.82 μm, 1.85 μm, 1.86 μm, 1.89 μm, 1.91 μm, 1.94 μm, 1.96 μm, 1.98 μm, 2.00 μm, 2.02 μm, 2.05 μm, 2.06 μm, 2.08 μm m, 2.1μm, 2.12μm, 2.15μm, 2.17μm, 2.19μm, 2.20μm, 2.23μm, 2.25μm, 2.28μm m, 2.30μm, 2.34μm, 2.38μm, 2.39μm, 2.45μm, 2.47μm, 2.52μm, 2.58μm, 2.62μm m, 2.65μm, 2.67μm, 2.73μm, 2.78μm, 2.79μm, 2.81μm, 2.85μm, 2.87μm, 2.9μ m, 2.91μm, 2.94μm, 2.96μm, 2.98μm, 3.0μm, 3.04μm, 3.08μm, 3.09μm, 3.12μm , 3.15μm, 3.18μm, 3.20μm, 3.25μm, 3.28μm, 3.30μm, 3.34μm, 3.38μm, 3.39μm m, 3.45μm, 3.47μm, 3.52μm, 3.58μm, 3.62μm, 3.65μm, 3.67μm, 3.73μm, 3.78μm m, 3.79μm, 3.81μm, 3.85μm, 3.87μm, 3.9μm, 3.91μm, 3.94μm, 3.96μm, 3.98μm m, 4.0μm, 4.04μm, 4.08μm, 4.09μm, 4.12μm, 4.15μm, 4.18μm, 4.20μm, 4.25μm , 4.28μm, 4.30μm, 4.34μm, 4.38μm, 4.39μm, 4.45μm, 4.47μm, 4.52μm, 4.58μm m, 4.62μm, 4.65μm, 4.67μm, 4.73μm, 4.78μm, 4.79μm, 4.81μm, 4.85μm, 4.87μm m, 4.9μm, 4.91μm, 4.94μm, 4.96μm, 4.98μm, 5.0μm, 5.04μm, 5.08μm, 5.09μm, 5.12μm, 5.15μm, 5.18μm, 5.20μm, 5.25μm, 5.28μm, 5.3μm, 5.38μm, 5.4μm, 5.42μm, 5.45μm, 5.48μm, 5.49μm, 5.55μm, 5.56μm, 5.59μm, 5.62μm, 5.65μm, 5.67μm, 5.68μm, 5.7μm, 5.72μm, 5.75μm or 5.78μm, etc.
[0081] In the above embodiment, the particle size distribution of the lithium supplement agent is relatively concentrated, and when applied to the positive electrode sheet, the distribution uniformity in the positive electrode sheet can be improved.
[0082] In some embodiments, the content of magnetic foreign matter in the lithium supplement is 0.11ppm~0.13ppm.
[0083] In some embodiments, the free lithium content of the lithium supplement is 321 ppm to 599 ppm.
[0084] In some embodiments, at 25°C and humidity less than or equal to 10%, the first charge specific capacity of the lithium supplement at a 0.1C rate is 701.3 mAh / g~760 mAh / g, preferably 714 mAh / g~760 mAh / g; at 25°C and humidity less than or equal to 10%, the first discharge specific capacity of the lithium supplement at a 0.1C rate is 4.6 mAh / g~16.7 mAh / g.
[0085] For example, under the conditions of 25°C and humidity less than or equal to 10%, the first charge specific capacity of the lithium supplement at 0.1C rate is 701.3 mAh / g, 703 mAh / g, 705 mAh / g, 710 mAh / g, 715 mAh / g, 718 mAh / g, 720 mAh / g, 723 mAh / g, 728 mAh / g, 731 mAh / g, 735 mAh / g, 739 mAh / g, 740 mAh / g, 745 mAh / g, 749 mAh / g, 750 mAh / g, 752 mAh / g, 756 mAh / g, 758 mAh / g, 759 mAh / g or 759.9 mAh / g; under the conditions of 25°C and humidity less than or equal to 10%, the first discharge specific capacity of the lithium supplement at 0.1C rate is 4.6 mAh / g, 4.9 mAh / g, 5.2 mAh / g, 5.5 mAh / g, 5.8 mAh / g, 5.9 mAh / g, 6.1mAh / g, 6.2 mAh / g, 6.5 mAh / g, 6.8mAh / g, 6.9 mAh / g, 7.2 mAh / g, 7.5 mAh / g, 7.8 mAh / g, 7.9 mAh / g, 8.1mAh / g, 8.2mAh / g, 8.5 mAh / g, 8.8mAh / g, 9.1mAh / g, 9.2 mAh / g, 9.5 mAh / g, 9.8mAh / g, 9.9 mAh / g, 10.2mAh / g, 10.5 mAh / g, 10.8 mAh / g, 10.9 mAh / g, 11.1mAh / g, 11.2 mAh / g, 11.5 mAh / g, 11.8mAh / g, 12.1 mAh / g, 12.5 mAh / g, 12.6 mAh / g, 12.9 mAh / g, 13.2 mAh / g, 13.5 mAh / g, 13.8 mAh / g, 13.9 mAh / g, 14.1mAh / g, 14.2 mAh / g, 14.5 mAh / g, 14.8mAh / g, 14.9 mAh / g, 15.2 mAh / g, 15.5 mAh / g, 15.8 mAh / g, 15.9 mAh / g, 16.1mAh / g, 16.2 mAh / g, 16.5 mAh / g or 16.7mAh / g, etc.
[0086] In some embodiments, under the conditions of 25°C and humidity less than or equal to 10%, the first charge specific capacity of the lithium supplement at a 1C rate is 662 mAh / g~728 mAh / g, preferably 689 mAh / g~728 mAh / g; under the conditions of 25°C and humidity less than or equal to 10%, the first charge specific capacity of the lithium supplement at a 1C rate is 2.1 mAh / g~6.9 mAh / g.
[0087] For example, under the conditions of 25° C. and humidity less than or equal to 10%, the first charge specific capacity of the lithium supplement at a rate of 1C is 672.4 mAh / g, 675 mAh / g, 678 mAh / g, 679 mAh / g, 680 mAh / g, 685 mAh / g, 687 mAh / g, 689 mAh / g, 691 mAh / g, 693 mAh / g, 695 mAh / g, 699 mAh / g, 700 mAh / g, 701 mAh / g, 701.3 mAh / g, 703 mAh / g, 705 mAh / g, 710 mAh / g, 715 mAh / g, 718 mAh / g, 720 mAh / g, 723 mAh / g, 725 mAh / g, 726 mAh / g, 727 mAh / g or 728 mAh / g. mAh / g, etc.; under the conditions of 25°C and humidity less than or equal to 10%, the first discharge specific capacity of the lithium supplement at 0.1C rate is 2.1 mAh / g, 2.3 mAh / g, 2.5 mAh / g, 2.6 mAh / g, 2.8 mAh / g, 2.9 mAh / g, 3.0 mAh / g, 3.2 mAh / g, 3.4 mAh / g, 3.7 mAh / g, 3.8 mAh / g, 4.0 mAh / g, 4.1 mAh / g, 4.3 mAh / g, 4.5 mAh / g, 4.6 mAh / g, 4.8 mAh / g, 4.9 mAh / g, 5.2 mAh / g, 5.5 mAh / g, 5.8 mAh / g, 5.9 mAh / g, 6.1 mAh / g, 6.2 mAh / g, 6.5 mAh / g, 6.8 mAh / g or 6.9 mAh / g, etc.
[0088] In some embodiments, after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 4 hours, the lithium supplement has a first charge specific capacity of 643 mAh / g~750 mAh / g at a rate of 0.1C, preferably 671 mAh / g~750 mAh / g, for example, 651.5 mAh / g, 671.5 mAh / g, 674.3 mAh / g, 683.2 mAh / g, 701.4 mAh / g, 749.5 mAh / g, etc.; after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 4 hours, the lithium supplement has a first discharge specific capacity of 2.4 mAh / g~11.2 mAh / g at a rate of 0.1C, for example, 3.1 mAh / g, 3.2 mAh / g, 4.8 mAh / g, 4.9 mAh / g, 8.1 mAh / g, 10.1 mAh / g, etc.
[0089] In some embodiments, after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 4 hours, the lithium supplement has a first charge specific capacity of 601 mAh / g~720 mAh / g at a rate of 1C, preferably 643 mAh / g~720 mAh / g, for example, 635.3 mAh / g, 687.5 mAh / g, 698.1 mAh / g, 701.3 mAh / g, etc.; after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 4 hours, the lithium supplement has a first discharge specific capacity of 1.4 mAh / g~6.2 mAh / g at a rate of 1C, for example, 1.6 mAh / g, 2.1 mAh / g, 4.2 mAh / g, 6.1 mAh / g, etc.
[0090] In some embodiments, after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 12 hours, the lithium supplement has a first charge specific capacity of 587 mAh / g to 749 mAh / g at a rate of 0.1C, preferably 641 mAh / g to 749 mAh / g, for example, 601.5 mAh / g, 633.8 mAh / g, 646.4 mAh / g, 700.2 mAh / g, 707.8 mAh / g, 748.1 mAh / g, etc.; after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 12 hours, the lithium supplement has a first discharge specific capacity of 2.6 mAh / g to 8.6 mAh / g at a rate of 0.1C, for example, 2.7 mAh / g, 3.2 mAh / g, 3.6 mAh / g, 5.3 mAh / g, 7.3 mAh / g, 8.1 mAh / g, etc.
[0091] In some embodiments, after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 12 hours, the lithium supplement has a first charge specific capacity of 497 mAh / g~718 mAh / g at a rate of 1C, preferably 617 mAh / g~718 mAh / g, for example, 511.3 mAh / g, 604.8 mAh / g, 614.6 mAh / g, 683.7 mAh / g, etc.; after being placed at 25°C±1°C and humidity less than or equal to 85%±5% for 12 hours, the lithium supplement has a first discharge specific capacity of 1.9 mAh / g~5.9 mAh / g at a rate of 1C, for example, 2.1 mAh / g, 2.4 mAh / g, 4.2 mAh / g, 5.1 mAh / g, 5.9 mAh / g, etc.
[0092] In some embodiments, the above-mentioned first charge specific capacity and first discharge specific capacity of the lithium supplement agent are obtained by preparing a positive electrode sheet having the lithium supplement agent, assembling the positive electrode sheet into a button battery and conducting testing.
[0093] In some embodiments, the positive electrode plate includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material is a lithium supplement as described above. The binder is preferably PVDF (polyvinylidene fluoride), and other adhesive materials suitable for positive electrode plates can also be used. The conductive agent is preferably a carbon conductive material, such as conductive carbon black (SP). The above-mentioned positive electrode active material, binder, and conductive agent are proportioned in a suitable mass ratio, and an aluminum sheet is used as a current collector to prepare a positive electrode plate. The mass ratio of the positive electrode active material, binder, and conductive agent can be 78:8:14.
[0094] In a second aspect, the present application provides a method for preparing a lithium supplement, such as Figure 1 As shown, including:
[0095] S11, providing lithium-rich lithium iron oxide material;
[0096] S12, forming a coating layer on the surface of the lithium iron-rich lithium material; the material of the coating layer includes: lithium pyrophosphate.
[0097] In the preparation method of the lithium supplement provided in the embodiment of the present application, a coating layer is formed on the surface of the lithium-rich ferrite material, and the material of the coating layer includes: lithium pyrophosphate, so as to obtain a lithium supplement, and the preparation method is simple and easy. The surface of the lithium-rich ferrite material of the lithium supplement prepared in this way is coated with a coating layer having lithium pyrophosphate. On the one hand, the lithium pyrophosphate is an ion conductor, which provides a deintercalation channel for lithium ions while providing part of the capacity, facilitates the movement of lithium ions during the battery charge-discharge process, and improves the lithium ion transmission and conduction performance. On the other hand, the lithium pyrophosphate protects the lithium-rich ferrite material, reduces the contact between the lithium-rich ferrite material and the air, thereby improving the air stability of the lithium-rich ferrite material, achieving the effect of improving the air stability and safety stability of the lithium supplement, and enhancing the lithium supplement effect of the lithium supplement.
[0098] The above-mentioned lithium-rich lithium iron oxide material can be obtained through commercial channels or can be made by oneself.
[0099] In some embodiments, the lithium supplement agent as described above is obtained by the preparation method of the lithium supplement agent provided in the present application.
[0100] In some embodiments, S11, the step of providing the lithium-rich lithium ferrite material may include:
[0101] S111, providing a first lithium salt and a ferrous salt;
[0102] S112, mixing the first lithium salt and the ferrous salt, and calcining them under the protection of a protective gas to obtain a lithium-rich lithium ferrite material.
[0103] In the above embodiment, after the first lithium salt and the ferrous salt are mixed, they are calcined under the protection of a protective gas, so as to facilitate more effective fusion of lithium and iron elements and reduce the generation of impurities, thereby improving the product performance of the obtained lithium supplement.
[0104] In some embodiments, the first lithium salt includes lithium nitrate, the ferrous salt is ferrous oxalate, and the ferrous oxalate includes titanium.
[0105] In the above embodiment, lithium nitrate and ferrous oxalate are used as raw materials and calcined under the protection of protective gas. Compared with the use of lithium salts or lithium oxides and trivalent iron oxides to obtain lithium-rich lithium iron oxide in the related art, on the one hand, there is no need to use a large amount of high-cost lithium oxide, and the cost is lower; on the other hand, when lithium nitrate and ferrous oxalate react, the calcination temperature is low and the calcination time is shorter, which is beneficial to saving energy; at the same time, due to the redox reaction between lithium nitrate and ferrous oxalate, nitrogen oxides are reduced to nitrogen gas, which is beneficial to reducing the generation of nitrogen oxides, reducing environmental pollution and corresponding governance costs; in addition, the lithium nitrate and ferrous oxalate are used as raw materials, and the lithium-rich lithium iron oxide material prepared by calcining under the protection of protective gas has less agglomeration, making subsequent crushing more convenient, and it is easy to prepare lithium-rich lithium iron oxide materials with a large specific surface area, which is beneficial to improving the electrochemical properties of lithium-rich lithium iron oxide materials and enhancing the lithium replenishment effect of lithium replenishers. In addition, when the ferrous salt includes titanium, it is convenient to introduce titanium into the lithium-rich lithium ferrite material, which is beneficial to improving the electrochemical properties and thermal stability of the lithium-rich lithium ferrite material and further improving the lithium supplementation effect.
[0106] The reaction equation of the redox reaction between the lithium nitrate and ferrous oxalate is shown in the following formula (1):
[0107] LiNO 3 +FeC 2 O 4 → Li 5 FeO 4 +NO 2 +N 2 +CO 2 Formula (1)
[0108] In some embodiments, the ferrous oxalate may be doped with 0.5% to 4% by mass of the Ti element, preferably 1% to 3% by mass of the Ti element. For example, in the ferrous oxalate, the mass percentage of the Ti element is 1%, 2% or 3%.
[0109] In some embodiments, the particle size of ferrous oxalate may be 5 μm to 10 μm, and the particle size of lithium nitrate may be 5 μm to 10 μm. For example, the particle size of ferrous oxalate may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, and the particle size of lithium nitrate may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc.
[0110] In the above embodiment, by controlling the particle size of ferrous oxalate to 5 μm ~ 10 μm and the particle size of lithium nitrate to 5 μm ~ 10 μm, it is beneficial to ensure that lithium nitrate and ferrous oxalate are mixed more effectively and fully react at a lower calcination temperature, reduce the generation of nitrogen oxides, and reduce the agglomeration of lithium-rich lithium ferrate material, so as to obtain lithium-rich lithium ferrate material with good dispersion performance and large specific surface area, thereby improving the lithium replenishment effect of the lithium replenisher.
[0111] In some embodiments, in order to improve the reaction conversion rate and reduce the residual raw materials, the ratio of the total amount of lithium in the first lithium salt to the total amount of iron and titanium in the ferrous salt is (5.0-5.3): 1. Preferably, the ratio of the total amount of lithium in the first lithium salt to the total amount of iron and titanium in the ferrous salt is (5.05-5.2): 1. For example, the ratio of the total amount of lithium in the first lithium salt to the total amount of iron and titanium in the ferrous salt can be 5.0: 1, 5.05: 1, 5.1: 1, 5.2: 1 or 5.3: 1, etc.
[0112] In some embodiments, the first lithium salt and the ferrous salt can be mixed using an oblique mixer or a double-screw mixer, and the mixing time can be 2 h to 4 h. For example, the mixing time can be 2 h, 3 h or 4 h, which can achieve effective mixing.
[0113] In S112, during the calcination process, by introducing a protective gas, on the one hand, the first lithium salt and the ferrous salt can be kept to undergo a redox reaction under the protection of the protective gas, thereby improving the conversion rate of the redox reaction between the first lithium salt and the ferrous salt, reducing the generation of impurities and improving the purity of the obtained lithium-rich lithium ferrite material; on the other hand, the protective gas can also promptly remove the waste gas (such as nitrogen oxides) generated during the calcination process, further improving the yield of the obtained lithium-rich lithium ferrite material.
[0114] During the calcination process, the flow rate of the protective gas can be 0.1 m / s to 0.3 m / s. At the same time, an induced draft fan can be used to circulate the protective gas in the reactor and remove the waste gas. For example, the flow rate of the protective gas can be 0.1 m / s, 0.2 m / s or 0.3 m / s.
[0115] In some embodiments, the protective gas may include nitrogen, argon and / or helium, etc.
[0116] In some embodiments, in S112, the first lithium salt and the ferrous salt are mixed, and calcined under the protection of a protective gas to obtain a lithium-rich lithium ferrate material, the preparation method further includes: using a hydrogen peroxide solution with a mass fraction of 0.1% to 0.3% of hydrogen peroxide to absorb the waste gas brought out by the protective gas to obtain a dilute nitric acid solution. The dilute nitric acid solution can be used to continue to prepare lithium nitrate, and the prepared lithium nitrate can be used as the first lithium salt for recycling in the preparation of lithium-rich lithium ferrate material, realizing the recycling of waste gas, which is conducive to reducing process costs and reducing environmental pollution.
[0117] In some embodiments, when a dilute nitric acid solution is obtained by absorbing exhaust gas with a hydrogen peroxide solution, lithium carbonate can be added to the dilute nitric acid solution to dissolve it, and then lithium nitrate crystals can be obtained by concentration and crystallization to prepare lithium nitrate.
[0118] In some embodiments, the calcination may include: a first stage and a second stage performed sequentially;
[0119] In the first stage, the calcination temperature is 200℃~400℃, and the calcination holding time is 3h~5h;
[0120] In the second stage, the calcination temperature is 600℃~700℃, and the calcination holding time is 4 h~6h.
[0121] For example, in the first stage, the calcination temperature can be 200°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 380°C, 390°C or 400°C, and the calcination holding time can be 4h, 5h or 6h.
[0122] In the second stage, the calcination temperature can be 600°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, and the calcination holding time can be 4h, 5h or 6h.
[0123] In the above embodiment, by setting up two calcination stages, it is beneficial to allow the redox reaction of the first lithium salt and the ferrous salt to fully proceed in the first stage while allowing the generated water vapor, carbon dioxide, nitrogen oxides, etc. to be discharged as soon as possible, thereby reducing the reaction of these gases with lithium; in the second stage, by further increasing the reaction temperature, it is beneficial to allow the first lithium salt and the ferrous salt to further fully react, thereby obtaining a lithium-rich lithium ferrate material with improved purity.
[0124] In some embodiments, in the first stage, the heating rate of calcination may be 100°C / h to 200°C / h, and in the second stage, the heating rate of calcination may be 50°C / h to 100°C / h. For example, in the first stage, the heating rate of calcination may be 100°C / h, 120°C / h, 130°C / h, 150°C / h, 160°C / h, 180°C / h or 200°C / h, etc., and in the second stage, the heating rate of calcination may be 50°C / h, 60°C / h, 70°C / h, 80°C / h, 90°C / h or 100°C / h, etc.
[0125] In some embodiments, after the calcination is completed, the material can be cooled to a temperature less than or equal to 80° C. before being discharged.
[0126] In some embodiments, in order to further improve the lithium replenishing performance of the lithium replenishing agent and the coating effect of lithium pyrophosphate on the surface of the lithium-rich lithium ferrite material, the particle size of the lithium-rich lithium ferrite material can be 1 μm to 5 μm.
[0127] In some embodiments, the material after the calcination is cooled to a temperature less than or equal to 80° C. to obtain a cooled material, and the cooled material is crushed to obtain a lithium-rich lithium ferrite material.
[0128] In some embodiments, after discharging, before forming a coating layer on the surface of the lithium-rich iron phosphate material, the lithium-rich iron phosphate material can be transported to a sealed reactor by negative pressure conveying. Specifically, in order to reduce the contact between the lithium-rich iron phosphate material and the air, the lithium-rich iron phosphate material can be transported to a pulverizer by negative pressure conveying for pulverization. After the pulverization is completed, the lithium-rich iron phosphate material with a particle size of 1 μm to 5 μm is obtained. In order to further reduce the contact between the lithium-rich iron phosphate material and the air, during the above-mentioned pulverization process, a protective gas can be introduced into the pulverizer to protect the lithium-rich iron phosphate material. Among them, the protective gas can be, for example, nitrogen with a dew point ≤-75°C. In order to reduce the pollution of the lithium-rich iron phosphate material by the pulverizer, the part that contacts the lithium-rich iron phosphate material during pulverization in the pulverizer can be made of ceramic material.
[0129] Similar to the above-mentioned pulverization, in order to further reduce the contact of the lithium-rich lithium iron oxide material with air before reacting with the first lithium salt and the pyrophosphate source in the sealed reactor, a protective gas may be introduced into the sealed reactor during the negative pressure transportation process to protect the lithium-rich lithium iron oxide material transported to the sealed reactor. The protective gas may be nitrogen with a dew point of ≤-75°C, for example.
[0130] In some embodiments, the specific implementation method of forming the coating layer on the surface of the lithium-rich lithium iron phosphate material is not limited, and all preparation methods that can coat lithium pyrophosphate on the surface of the lithium-rich lithium iron phosphate material are within the protection scope of this application.
[0131] In some embodiments, forming a coating layer on the surface of the lithium ferrite-rich lithium material may include:
[0132] The second lithium salt, the pyrophosphate source, and the first solvent are mixed to obtain a first reaction material;
[0133] The lithium iron oxide material rich in lithium is mixed with the first reaction material, and subjected to a first impurity removal treatment to obtain a lithium supplement agent.
[0134] In the above embodiment, the lithium iron phosphate-rich material is mixed with a second lithium salt and a pyrophosphate source, and the second lithium salt and the pyrophosphate source are reacted to obtain lithium pyrophosphate. At the same time, the lithium pyrophosphate can be deposited on the surface of the lithium iron phosphate-rich material to form a coating layer on the surface of the lithium iron phosphate-rich material. After a first impurity removal treatment, a lithium supplement is obtained.
[0135] In some embodiments, the lithium iron-rich lithium material, the second lithium salt and the pyrophosphate source can be mixed in a sealed reactor, and the second lithium salt and the pyrophosphate source can undergo a double decomposition reaction under the protection of a protective gas. For example, before the reaction, nitrogen with a dew point of ≤-75°C can be introduced into the sealed reactor to replace the air in the sealed reactor, so that the humidity in the sealed reactor is ≤5%, and then, by heating the sealed reactor, the second lithium salt and the pyrophosphate source can react at a preset temperature.
[0136] In this process, the mixed solution of the lithium iron-rich material, the second lithium salt and the pyrophosphate source can be stirred and heated under stirring, which is conducive to the full reaction of the second lithium salt and the pyrophosphate source to obtain lithium pyrophosphate, thereby achieving the deposition of lithium pyrophosphate on the surface of the lithium iron-rich material. The stirring speed can be 150 r / min~300 r / min.
[0137] In some embodiments, the second lithium salt includes at least one of lithium acetate, lithium chloride, lithium nitrate and lithium citrate.
[0138] In the above embodiment, at least one of lithium acetate, lithium chloride, lithium nitrate and lithium citrate is used as the second lithium salt. During the reaction of the second lithium salt and the pyrophosphate source, the azeotropic principle of the first solvent and the acid corresponding to the anion in the second lithium salt can be used to achieve the decomposition and / or volatilization of the anion of the second lithium salt, as well as the precipitation and crystallization of lithium pyrophosphate, and heterogeneous nucleation is easy to occur on the surface of the lithium-rich lithium iron oxide material. During the heterogeneous nucleation of lithium pyrophosphate on the surface of the lithium-rich lithium iron oxide, as the first solvent evaporates, lithium ions and pyrophosphate slowly combine, and the supersaturation of lithium pyrophosphate can be maintained at a low level, so that the lithium pyrophosphate can be slowly crystallized and deposited on the surface of the lithium-rich lithium iron oxide material, making the coating more dense and complete.
[0139] In some embodiments, the pyrophosphate source includes at least one of pyrophosphoric acid, ammonium pyrophosphate, and ammonium hydrogen pyrophosphate.
[0140] In the above embodiment, at least one of pyrophosphate, ammonium pyrophosphate and ammonium hydrogen pyrophosphate is used as the pyrophosphate source, and the products other than lithium pyrophosphate generated by the reaction of the second lithium salt and the pyrophosphate source are easy to decompose and volatilize, which facilitates the precipitation and crystallization of lithium pyrophosphate on the surface of the lithium iron-rich material while reducing the introduction of impurities.
[0141] For example, the second lithium salt and the pyrophosphate source may undergo a double decomposition reaction to generate lithium pyrophosphate and a volatile gas. The volatile gas may be removed by the first impurity removal treatment, thereby obtaining a lithium supplement.
[0142] In some embodiments, the first solvent includes: ethanol.
[0143] In the above embodiment, ethanol is used as the first solvent, which has a low boiling point and is easy to evaporate.
[0144] In some embodiments, the initial addition amount of the first solvent is 5 to 15 times the mass of the second lithium salt.
[0145] In the above embodiment, by controlling the initial addition amount of the first solvent to be 5 to 15 times the mass of the second lithium salt, the precipitation rate of lithium pyrophosphate can be controlled to make the lithium pyrophosphate coating more complete.
[0146] Among them, the above-mentioned lithium iron phosphate-rich material can be in powder form, the second lithium salt and pyrophosphate can be dissolved in the first solvent, and the second lithium salt and pyrophosphate are reacted after being heated to a preset temperature under stirring, and the solvent is volatilized by stirring, so that the lithium pyrophosphate is deposited on the surface of the lithium iron phosphate-rich material.
[0147] In some embodiments, the first impurity removal treatment includes evaporating the first solvent, solid-liquid separation, drying, screening and iron removal.
[0148] In the above embodiment, by evaporating the first solvent, the volatile gas generated after the lithium-rich lithium iron oxide material and the first reaction material are mixed can be removed together, thereby obtaining lithium-rich lithium iron oxide coated with lithium pyrophosphate; at the same time, by evaporating and removing the first solvent, the lithium pyrophosphate is gradually precipitated and coated on the surface of the lithium-rich lithium iron oxide material, and then through solid-liquid separation, drying, screening and iron removal treatment, a lithium supplement with higher purity is obtained.
[0149] In some embodiments, the temperature for evaporating the first solvent may be 80° C. to 120° C. For example, the temperature for evaporating the first solvent may be 80° C., 90° C., 100° C., 110° C. or 120° C.
[0150] In the above embodiment, the evaporation temperature is controlled to facilitate azeotropy of the first solvent and the anion of the second lithium salt.
[0151] In some embodiments, the volume of the first solvent after evaporation is reduced to 1 / 4 to 1 / 3 of the initial volume. For example, the volume of the first solvent after evaporation is reduced to 1 / 4, 3 / 10 or 1 / 3 of the initial volume.
[0152] By controlling the volume of the first solvent to decrease to 1 / 4 to 1 / 3 of the initial volume after evaporation, an appropriate amount of lithium pyrophosphate can be controlled to precipitate and coat the surface of the lithium ferrite-rich lithium material, thereby effectively controlling the thickness of the coating layer.
[0153] In some embodiments, in order to facilitate the evaporation of the first solvent and the volatile gas, an exhaust pipe may be connected to the sealed reaction vessel to volatilize the evaporated solvent and the volatile gas and recover them through condensation.
[0154] In some embodiments, the ratio of the amount of the lithium ferrite-rich material, the lithium element in the second lithium salt, and the pyrophosphate in the pyrophosphate source is 1: (0.1-0.15): (0.025-0.04). For example, the ratio of the amount of the lithium ferrite-rich material, the lithium element in the second lithium salt, and the pyrophosphate in the pyrophosphate source can be 1: 0.1: 0.025, 1: 0.1: 0.03, 1: 0.1: 0.035, 1: 0.1: 0.04, 1: 0.12: 0.025, 1: 0.12: 0.03, 1: 0.12: 0.035, 1: 0.12: 0.04, 1: 0.15: 0.025, 1: 0.15: 0.03, 1: 0.15: 0.035 or 1: 0.15: 0.04, etc.
[0155] In the above embodiment, by controlling the molar ratio of the lithium-rich lithium ferrite material, the lithium element in the second lithium salt and the pyrophosphate ion in the pyrophosphate source to be 1:(0.1~0.15):(0.025~0.04), it is beneficial to form an appropriate amount of lithium pyrophosphate as a coating layer on the surface of the lithium-rich lithium ferrite material, so that the coating is more complete, and the contact between the lithium-rich lithium ferrite material and the air is effectively reduced, thereby effectively improving the capacity and stability of the lithium supplement when used.
[0156] In some embodiments, the coating is completed when the volume of the first solvent evaporates to 1 / 4 to 1 / 3 of the initial volume, and the solvent can be removed by centrifugation and drying, and then the lithium supplement can be obtained by screening and iron removal.
[0157] In some embodiments, the drying can be performed under protective gas protection. For example, the centrifuged material can be placed in a nitrogen oven for drying. The dew point of the nitrogen introduced into the nitrogen oven can be ≤-75°C, the drying temperature can be 100°C to 150°C, and the drying time can be 3 h to 6 h. After the drying is completed, the lithium supplement is obtained by screening, iron removal and packaging.
[0158] In some embodiments, during the above-mentioned centrifugation, drying, screening, iron tapping and packaging processes, the centrifuge used for centrifugation, the nitrogen oven used for drying, the vibrating screen used for screening, the iron tapping device used for iron removal and the packaging machine used for packaging can all be set in a constant temperature and humidity room, which can improve the quality stability of the finished product. For example, the humidity in the constant temperature and humidity room can be controlled within ≤5%, and the temperature can be 20°C~30°C.
[0159] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector, and a positive electrode material disposed on at least one side of the current collector along its thickness direction, wherein the positive electrode material comprises the lithium supplement agent as described in the first aspect.
[0160] In the positive electrode plate provided in the embodiment of the present application, since the positive electrode material contained in the positive electrode plate includes the lithium supplement agent as described in the first aspect, the positive electrode plate can achieve effective lithium supplementation, and can improve the safety stability and air stability of the battery during the lithium supplementation process, while maintaining the battery with high lithium ion transmission and conduction performance.
[0161] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator; wherein the positive electrode sheet may be the positive electrode sheet described in the third aspect.
[0162] In the secondary battery provided in the embodiment of the present application, since the secondary battery includes the positive electrode plate as described in the third aspect, the secondary battery has higher safety stability and air stability during the lithium replenishment process, and has higher lithium ion transmission and conduction performance.
[0163] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising: a plurality of batteries connected in series and / or in parallel, at least one battery being a secondary battery as described in the fourth aspect.
[0164] In the electric device provided in the embodiment of the present application, since the battery included in the electric device includes the secondary battery as described in the fourth aspect, the electric device has good safety stability and power consumption stability.
[0165] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0166] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0167] Example 1
[0168] The preparation method of the lithium supplement provided in Example 1 is as follows:
[0169] Step 1), lithium nitrate and ferrous oxalate are mixed, and calcined at high temperature under nitrogen protection to obtain lithium-rich lithium ferrate; ferrous oxalate is doped with 2% Ti element by mass, the particle size of ferrous oxalate is 8.2 μm, the total amount of lithium element in lithium nitrate and the total amount of iron element and titanium element in ferrous oxalate is 5.1:1, the particle size of lithium nitrate is 8.5 μm, an oblique mixer is used, the mixing time is 3 hours, and during the calcination process, in the first stage: the heating rate is 150°C / h, and the temperature is raised to The temperature is 300℃, and it is kept at this temperature for 4h. The second stage: continue to heat up to 650℃, the heating rate is 80℃ / h, the sintering time is 5h, and nitrogen is introduced to make the gas flow rate in the furnace 0.2m / s. At the same time, the exhaust gas is led out by an induced draft fan, and a 0.2% by mass hydrogen peroxide solution is used to absorb it to obtain a dilute nitric acid solution. After returning and adding lithium carbonate to dissolve, it is concentrated and crystallized to prepare lithium nitrate; the sintered material is cooled to a material temperature of 80℃ and then discharged;
[0170] Step 2), the lithium iron oxide rich prepared in step 1) is transported to the pulverizer by negative pressure for crushing. During the negative pressure conveying process, nitrogen with a dew point of ≤-75°C is used for air replenishment. During the crushing process, nitrogen with a dew point of ≤-75°C is introduced into the pulverizer for protection. The parts in the pulverizer that are in contact with the lithium iron oxide rich are all made of ceramic materials. The lithium iron oxide rich is crushed to a particle size of 2.7μm, and then the crushing is stopped. Then, anhydrous ethanol is added to the sealed reactor, and then lithium acetate and pyrophosphoric acid are added, and the slurry is stirred to completely dissolve the lithium acetate and pyrophosphoric acid. The crushed material is transported to the sealed reactor. At the same time, nitrogen with a dew point of ≤-75°C is first introduced to replace the air in the sealed reactor, so that the humidity in the sealed reactor is ≤5%, and then the temperature is raised under stirring, and the stirring speed is 200r / min, and an exhaust pipe is set to evaporate the ethanol and acetic acid vapors that evaporate later and condense and recover them. The ratio of the amount of lithium iron oxide, lithium acetate and pyrophosphate added is 1:0.12:0.04, and the amount of anhydrous ethanol added is 10 times the mass of lithium acetate; heated to 100°C under stirring, stirred until the volume of ethanol evaporates to 1 / 4 of the original, and the reaction is terminated. The material in the sealed reactor is transported to the centrifuge through a pipeline to dry, and then washed with alcohol. The washed material is placed in a nitrogen oven for drying, and then screened, iron removed and packaged to obtain lithium iron oxide coated with lithium pyrophosphate. The mother liquor produced by centrifugal drying is returned to add anhydrous ethanol, lithium acetate and pyrophosphate for continued use. When drying in a nitrogen oven, the dew point of the nitrogen introduced is ≤-75°C, the drying temperature is 130°C, the drying time is 5h, and the centrifuge, oven, vibrating screen, iron remover and packaging machine are all set in a constant temperature and humidity room, the humidity is controlled within ≤5%, and the temperature is 20°C.
[0171] Example 2
[0172] The preparation method of the lithium supplement provided in Example 2 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0173] In step 1), ferrous oxalate is doped with 1% Ti element by mass, the particle size of ferrous oxalate is 5 μm, the molar ratio of lithium element in lithium nitrate to the total amount of iron element and titanium element in ferrous oxalate is 5.05:1, the particle size of lithium nitrate is 10 μm, an oblique mixer is used, and the mixing time is 4 hours. During the calcination process, the first stage: the heating rate is 100°C / h, the temperature is raised to 200°C, and the temperature is kept at this temperature for 3 hours. The second stage: the temperature is continued to be raised to 600°C, the heating rate is 50°C / h, the sintering time is 4 hours, nitrogen is introduced so that the gas flow rate in the furnace is 0.1m / s, and the exhaust gas is drawn out by an induced draft fan, and a 0.1% hydrogen peroxide solution is used to absorb it to obtain a dilute nitric acid solution, which is returned and dissolved by adding lithium carbonate, and then concentrated and crystallized to prepare lithium nitrate;
[0174] In step 2), the lithium iron-rich lithium ferrate is crushed to a particle size of 1.0 μm, and the crushing is stopped. During the stirring and slurrying process of the lithium iron-rich lithium ferrate, lithium acetate and pyrophosphate, the stirring speed is 150 r / min. Among them, the amount ratio of the added lithium iron-rich lithium ferrate, lithium acetate and pyrophosphate is 1:0.1:0.025, and the amount of anhydrous ethanol added is 5 times the mass of lithium acetate; heated to 80°C under stirring, stirred until the volume of ethanol evaporates to 1 / 3 of the original, and the reaction is terminated. When the lithium iron-rich lithium pyrophosphate-coated lithium ferrate is dried in a nitrogen oven, the dew point of the nitrogen is ≤-75°C, the drying temperature is 100°C, the drying time is 6h, and the centrifuge, oven, vibrating screen, iron remover and packaging machine are all set in a constant temperature and humidity room, the humidity is controlled within ≤5%, and the temperature is 30°C.
[0175] Example 3
[0176] The preparation method of the lithium supplement provided in Example 3 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0177] In step 1), ferrous oxalate is doped with 3% Ti by mass, the particle size of ferrous oxalate is 10 μm, the molar ratio of lithium element in lithium nitrate to the total amount of iron and titanium in ferrous oxalate is 5.2:1, the particle size of lithium nitrate is 5 μm, an oblique mixer is used, the mixing time is 2 hours, and during the calcination process, the first stage: the heating rate is 200°C / h, the temperature is raised to 400°C, and the temperature is kept at this temperature for 5 hours, the second stage: the temperature is continued to be raised to 700°C, the heating rate is 100°C / h, the sintering time is 6 hours, nitrogen is introduced so that the gas flow rate in the furnace is 0.3m / s, and the exhaust gas is drawn out by an induced draft fan, and a 0.3% by mass hydrogen peroxide solution is used to absorb it to obtain a dilute nitric acid solution, and lithium carbonate is added back to dissolve it, and then concentrated and crystallized to prepare lithium nitrate;
[0178] In step 2), the lithium iron-rich lithium ferrate is crushed to a particle size of 5 μm, and the crushing is stopped. During the stirring and slurrying process of the lithium iron-rich lithium ferrate, lithium acetate and pyrophosphate, the stirring speed is 300 r / min. Among them, the amount ratio of the added lithium iron-rich lithium ferrate, lithium acetate and pyrophosphate is 1:0.15:0.03, and the amount of anhydrous ethanol added is 15 times the mass of lithium acetate; heated to a temperature of 120°C under stirring, stirred until the volume of ethanol evaporates to 1 / 4 of the original, and the reaction is terminated. When the lithium iron-rich lithium pyrophosphate-coated lithium ferrate is dried in a nitrogen oven, the dew point of the nitrogen is ≤-75°C, the drying temperature is 150°C, the drying time is 3h, and the centrifuge, oven, vibrating screen, iron remover and packaging machine are all set in a constant temperature and humidity room, the humidity is controlled within ≤5%, and the temperature is 25°C.
[0179] Example 4
[0180] The preparation method of the lithium supplement provided in Example 4 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0181] In step 1), the ferrous oxalate is doped with 0.5% by mass of Ti element.
[0182] Example 5
[0183] The preparation method of the lithium supplement provided in Example 5 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0184] In step 1), ferrous oxalate is doped with 4% by mass of Ti element.
[0185] Example 6
[0186] The preparation method of the lithium supplement provided in Example 6 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0187] In step 1), the ferrous oxalate is not doped with Ti element.
[0188] Example 7
[0189] The preparation method of the lithium supplement provided in Example 7 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0190] In step 1), the total molar ratio of lithium in lithium nitrate to iron and titanium in ferrous oxalate is 5.0:1;
[0191] Example 8
[0192] The preparation method of the lithium supplement provided in Example 8 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0193] In step 1), the total molar ratio of lithium in lithium nitrate to iron and titanium in ferrous oxalate is 5.3:1;
[0194] Example 9
[0195] The preparation method of the lithium supplement provided in Example 9 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0196] In step 2), the molar ratio of lithium iron oxide, lithium acetate and pyrophosphate is 1:0.20:0.04.
[0197] Example 10
[0198] The preparation method of the lithium supplement provided in Example 10 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0199] In step 2), the molar ratio of lithium ferrite, lithium acetate and pyrophosphoric acid is 1:0.10:0.02.
[0200] Comparative Example 1
[0201] The preparation method of the lithium supplement provided in Comparative Example 1 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0202] The lithium-rich lithium iron oxide prepared in step 1) is directly crushed to a particle size of 2.7 μm and used as a lithium supplement.
[0203] Test methods and test results
[0204] 1. Test of chemical composition and physical and chemical indicators of lithium supplements
[0205] The chemical composition index and physicochemical index test of the lithium supplement provided in Examples 1 to 12 and Comparative Example 1 were performed, and the specific test results are shown in Table 1 below.
[0206] Table 1
[0207]
[0208] Among them, in the above Table 1, in the lithium supplement, the amount of Fe is determined by potentiometric titration, the amount of phosphorus is determined by quinoline phosphomolybdate weighing method, the amount of lithium, nickel, cobalt, chromium, and titanium is determined by inductively coupled plasma atomic emission spectrometry, and the content of free lithium is determined by potentiometric titration. The water content in the lithium supplement is obtained by KF method; the magnetic foreign matter in the lithium supplement can be collected by magnet, then dissolved by aqua regia, and tested on an atomic absorption spectrometer.
[0209] Table 2
[0210]
[0211] In Table 2, the tap density of the lithium supplement is measured by using a tap density meter, with the vibration number of 5000 times. The compaction density of the lithium supplement is measured by using a compaction density meter, with the test pressure of 3T and the pressing time of 30s. The pH value of the lithium supplement agent is obtained by acid-base potentiometric titration and testing with a pH meter; the specific surface area of the lithium supplement agent is obtained by testing with a BET specific surface area determination method, such as a nitrogen adsorption multi-point BET method; the D10 particle size, D50 particle size and D90 particle size in the particle size distribution of the lithium supplement agent can be obtained by testing with a laser particle size analyzer, and the laser particle size analyzer can be a Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK; wherein the D10 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 10%, the D50 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 50%, and the D90 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 90%.
[0212] In Table 2, the thickness of the coating layer is measured by transmission electron microscopy, and the coating rate of the coating layer is defined as the percentage of the coverage area of the coating layer on the surface of the particle (that is, the lithium iron oxide core of the above-mentioned embodiments 1 to 10) to the total surface area of the particle. The coating amount of the coating layer is measured by diffuse reflectance infrared Fourier transform spectroscopy. The coating rate can be calculated based on the coating amount and the cross-sectional area (also called cross-sectional area) of the coating layer. The calculation formula is: , where n represents the coating rate, M represents the coating amount, q represents the molecular weight of the coating material, and NA is a constant (6.023×10 23 ), a 0 Represents the cross-sectional area of the coating layer, S w Represents the specific surface area of the particles.
[0213] It can be seen from Table 1 and Table 2 that the lithium supplement agents provided in Examples 1 to 10 of the present application all have a lithium pyrophosphate coating layer coated on the surface of the lithium-rich lithium ferrate material. Compared with the lithium supplement agent provided in Comparative Example 1, the lithium supplement agents provided in Examples 1 to 10 have significantly reduced free lithium content, magnetic substance content, and residual alkali content, and significantly increased specific surface area due to the presence of the coating layer, which is beneficial to improving the capacity and lithium supplement effect of the lithium supplement agent when applied to a secondary battery; at the same time, the material obtained by the preparation method of the lithium supplement agent provided in Examples 1 to 10 has a weak degree of agglomeration after calcination, and is therefore easy to crush. The particle size of the lithium supplement agent finally obtained is smaller and more concentrated than the particle size of the lithium supplement agent provided in Comparative Example 1, which is also beneficial to improving the capacity and lithium supplement effect of the lithium supplement agent when applied to a secondary battery.
[0214] Further, by comparing Examples 1 to 5 with Example 6, it can be seen that by doping the Ti element in ferrous oxalate, the free lithium content is reduced, thereby improving the capacity and lithium supplement effect of the lithium supplement agent when applied to the secondary battery; by comparing Examples 1 to 5, Example 7 and Example 8, it can be seen that controlling the total amount ratio of the lithium element in lithium nitrate to the iron element and the titanium element in ferrous oxalate within the range of (5.05-5.2):1 is conducive to reducing the free lithium content and reducing the residual alkali content, while controlling the pH value of the lithium supplement agent is more appropriate, thereby improving the stability and lithium supplement effect of the lithium supplement agent when applied to the secondary battery; by comparing Examples 1 to 5, Example 9 and Example 10, it can be seen that controlling the amount ratio of lithium ferrite, lithium acetate and pyrophosphate within the range of 1: (0.1-0.15): (0.025-0.04) is conducive to reducing the free lithium content, reducing the residual alkali content, and controlling the pH value of the lithium supplement agent is more appropriate, thereby improving the stability and lithium supplement effect of the lithium supplement agent when applied to the secondary battery.
[0215] The lithium supplement provided in Examples 1 to 10 has a high compaction density, tap density and specific surface area, as well as a small and evenly distributed particle size, which is beneficial to improving the energy density of the lithium supplement. The coating layer of the lithium supplement provided in Examples 1 to 10 has a large thickness and a large coating rate, which protects the lithium-rich lithium ferrate material in the inner layer and reduces the contact between the lithium-rich lithium ferrate material and the air, which is beneficial to improving the stability of the lithium supplement. At the same time, lithium pyrophosphate as a coating layer is beneficial to improving the lithium ion conduction efficiency and maintaining a high capacity of the lithium supplement.
[0216] 2. Electrical performance index test of lithium supplement
[0217] The lithium supplement provided in Examples 1 to 10 and Comparative Example 1 were used as positive electrode active materials, respectively, and SP and PVDF were mixed in a ratio of 78%, 14% and 8% to prepare positive electrode sheets. The surface density of the positive electrode sheets was 3.5 mg / cm 2 .
[0218] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled into a button battery. The separator is glass fiber, the negative electrode sheet is a metal lithium sheet, and the solute of the electrolyte is LiPF 6 The solvent is a mixed solvent of EC (ethylene carbonate) and DEC (diethyl carbonate), LiPF 6 The concentration is 1 mol / L.
[0219] (1) After the prepared button battery was left standing for 10 hours at room temperature (25°C) and humidity ≤10%, the button battery was activated by charge-discharge. Then, the prepared button battery was tested for the first charge specific capacity and the first discharge specific capacity at a rate of 0.1C and the first charge specific capacity and the first discharge specific capacity at a rate of 1C at room temperature (25°C) with a nominal gram capacity of 700 mAh / g and a voltage range of 2.00V~4.35V. The test results of the first charge specific capacity and the first discharge specific capacity are shown in Table 3 below.
[0220] Table 3
[0221]
[0222] It can be seen from Table 3 that the button batteries with the lithium supplement provided in Examples 1 to 10 have larger initial charge capacities at 0.1C rate and 1C rate. For example, the button batteries with the lithium supplement provided in Examples 1 to 10 have initial charge specific capacities at 0.1C rate maintained at more than 700 mAh / g, and initial charge specific capacities at 1C rate maintained at more than 660 mAh / g.
[0223] By comparing the results of the button cells corresponding to the lithium supplement provided in Examples 1 to 5 and Example 6 in Table 3, it can be seen that by doping the Ti element, the initial charge specific capacity is improved, and when the doping ratio of the Ti element in ferrous oxalate is 1% to 3%, it is beneficial to obtain a higher initial charge specific capacity; by comparing the results of the button cells corresponding to the lithium supplement provided in Examples 1 to 3 and Examples 7 to 8 in Table 3, it can be seen that when the ratio of the total amount of iron and titanium in lithium nitrate to ferrous oxalate is (5.05:1 to 5.2):1, it is beneficial to obtain a higher initial charge specific capacity; by comparing the results of the button cells corresponding to the lithium supplement provided in Examples 1 to 3 and Examples 9 to 10 in Table 3, it can be seen that when the molar ratio of lithium-rich lithium ferrate, lithium acetate and pyrophosphate is in the range of 1:(0.1 to 0.15):(0.025 to 0.04), it is beneficial to obtain a higher initial charge specific capacity.
[0224] The method for performing a charge-discharge cycle test on the button battery prepared above at room temperature (25°C) in a voltage range of 2.00V to 4.35V is as follows:
[0225] (2) The prepared button battery was placed in an environment with a humidity of 85±5% and a temperature of 25±1°C for 4 hours and 12 hours, and then the electrical performance was tested. The specific test method was the same as the test method after standing for 10 hours at room temperature (25°C) and humidity ≤10%. The results of the first charge-discharge capacity test are shown in Table 4 below:
[0226] Table 4
[0227]
[0228]
[0229] As shown in Table 4, the button cells corresponding to the lithium supplement agents provided in Examples 1 to 10 still have a high initial charge specific capacity in a high humidity environment, and the change in the initial charge specific capacity measured after being placed in a high humidity environment for a long time is small, that is, the initial charge specific capacity retention rate is high in a high humidity environment, indicating that the lithium supplement agents provided in Examples 1 to 10 have good stability. However, since the lithium-rich ferrite in Comparative Example 1 is not coated, the lithium-rich ferrite directly contacts carbon dioxide, water vapor, etc. in the air, causing the lithium-rich ferrite to hydrolyze and decompose, thereby causing a sharp decline in capacity.
[0230] Comparing the results of the button cells corresponding to Examples 1 to 5 and Example 6 in Table 4, it can be seen that the doping of Ti element is conducive to the stability of the lithium supplement in a high humidity environment, that is, the doping of Ti element is conducive to improving the stability of the lithium supplement. Comparing the results of the button cells corresponding to Examples 1 to 5 and Examples 7 to 8 in Table 4, it can be seen that when the ratio of the total amount of iron and titanium in lithium nitrate and ferrous oxalate is in the range of (5.05 to 5.2): 1, it is more conducive to the stability of the lithium supplement in a high humidity environment. Comparing the results of the button cells corresponding to Examples 1 to 3 and Examples 9 to 10 in Table 4, it can be seen that when the ratio of the amount of lithium ferrite, lithium acetate and pyrophosphate is in the range of 1: (0.1 to 0.15): (0.025 to 0.04), it is more conducive to maintaining the stability of the lithium supplement.
[0231] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium supplement, characterized in that: include: A lithium-rich lithium iron oxide material, and a coating layer coated on the surface of the lithium-rich lithium iron oxide material; Wherein, the material of the coating layer includes: lithium pyrophosphate.
2. The lithium supplement according to claim 1, characterized in that: The lithium iron oxide-rich material includes titanium element.
3. The lithium supplement according to claim 1, characterized in that: The thickness of the coating layer is 10 nm to 50 nm; and / or the coating rate of the coating layer is greater than or equal to 94%.
4. A method for preparing a lithium supplement, characterized in that: include: Provide lithium-rich lithium iron oxide materials; forming a coating layer on the surface of the lithium-rich lithium ferrite material; Wherein, the material of the coating layer includes: lithium pyrophosphate.
5. The method for preparing a lithium supplement according to claim 4, characterized in that: The step of providing a lithium iron oxide-rich material comprises: providing a first lithium salt and a ferrous salt; The first lithium salt and the ferrous salt are mixed and calcined under the protection of a protective gas to obtain the lithium-rich lithium ferrate material.
6. The method for preparing a lithium supplement according to claim 5, characterized in that: The first lithium salt comprises lithium nitrate, the ferrous salt comprises ferrous oxalate, the ferrous oxalate comprises titanium, and the molar ratio of the lithium element in the first lithium salt to the total molar ratio of the iron element and the titanium element in the ferrous salt is (5.0-5.3):1; and / or The calcination includes a first stage and a second stage which are carried out sequentially; in the first stage, the calcination temperature is 200°C to 400°C, and the calcination holding time is 3 h to 5 h; in the second stage, the calcination temperature is 600°C to 700°C, and the calcination holding time is 4 h to 6 h.
7. The method for preparing a lithium supplement according to any one of claims 4 to 6, characterized in that: Forming a coating layer on the surface of the lithium-rich lithium ferrite material comprises: The second lithium salt, the pyrophosphate source, and the first solvent are mixed to obtain a first reaction material; The lithium iron oxide-rich material is mixed with the first reaction material, and subjected to a first impurity removal treatment to obtain the lithium supplement agent.
8. The method for preparing a lithium supplement according to claim 7, characterized in that: The first impurity removal treatment includes evaporating the first solvent, solid-liquid separation, drying, screening and iron removal; and / or, The preparation method of the lithium supplement meets at least one of the following conditions: (1) The molar ratio of the lithium iron-rich lithium material, the lithium element in the second lithium salt, and the pyrophosphate ion of the pyrophosphate source is 1:(0.1-0.15):(0.025-0.04); (2) The first solvent includes: ethanol; (3) The second lithium salt comprises: at least one of lithium acetate, lithium chloride, lithium nitrate and lithium citrate; (4) The pyrophosphate source comprises at least one of pyrophosphoric acid, ammonium pyrophosphate and ammonium hydrogen pyrophosphate; (5) The temperature for evaporating the first solvent is 80°C to 120°C.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode material arranged on at least one side of the current collector along the thickness direction thereof, wherein the positive electrode material comprises the lithium supplement agent according to any one of claims 1 to 3.
10. A secondary battery, characterized in that: include: Positive electrode sheet, negative electrode sheet and separator; Wherein, the positive electrode plate is the positive electrode plate as claimed in claim 9.
Citation Information
Cited By
Lithium supplement agent and preparation method thereof, positive plate, lithium ion battery, battery pack and electric equipment
CN120497343A
Modified lithium-rich manganese-based positive electrode material and preparation method thereof
CN121355240A